2022
DOI: 10.1186/s12940-022-00910-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of floods on undernutrition among children under five years of age in low- and middle-income countries: a systematic review

Abstract: Background Weather and climate-related disasters, including floods, impact undernutrition through multiple pathways, including food security, inadequate child care practices, and water and sanitation. This review aimed to provide systematic evidence of the impact of floods on undernutrition in children under five years of age in Low and Middle-income countries (LMICs). Methods We searched PubMed, Web of Science, Embase, MEDLINE, CINAHL and Scopus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(226 reference statements)
0
2
0
Order By: Relevance
“…The results of this study implied that although mothers are the primary caregivers of toddlers, fathers also significantly influence children's nutritional status. Fathers who are highly educated are likely to earn a higher income, so they have adequate food access 59,61,68,69 . Higher education was also associated with higher knowledge, attitudes, behavior, and awareness regarding children's nutritional adequacy, growth and development, hygiene behavior, and use of health facilities 29,32,40,42,61,66 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study implied that although mothers are the primary caregivers of toddlers, fathers also significantly influence children's nutritional status. Fathers who are highly educated are likely to earn a higher income, so they have adequate food access 59,61,68,69 . Higher education was also associated with higher knowledge, attitudes, behavior, and awareness regarding children's nutritional adequacy, growth and development, hygiene behavior, and use of health facilities 29,32,40,42,61,66 .…”
Section: Resultsmentioning
confidence: 99%
“…Flood events could also be indirectly associated with diarrhea risk. By devastating crops and livestock, floods may substantially reduce agricultural yield and increase undernutrition, 4 , 40 which could increase susceptibility to diarrheal infection, although the time course of this indirect association might be considerably longer than the aforementioned direct associations.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the 14 studies reported significant undernutrition outcomes due to food exposure. Six of the nine studies reported significant effects on stunting, four on wasting, and three on underweight (Noel A. C., 2022) [12]. Caroline Noel Agabiirwe, Noel A. C., Peter D., Constance M.T., Phalkey, R. K, 2022 Nutrition and flood According to Damar Bahadur Khadka, various fermented foods such as Sel roti, jand, mascara, kinema, gundruk, sinki, khalpi, dahi, mohi, gheu, chhurpi, somar, sidra, sukuti, and sukkako machha are prepared and consumed in Nepal.…”
Section: National Children Right Council 2020 Nutrition and Floodmentioning
confidence: 99%